Validation of the sport education scale for higher education students in the Indonesian version - Ginanjar, Agi; Burgueño, Rafael; Ramadhan, Riki; Larasaty, Gina (Journal Sport Area, 2024)
Background Problems: At the higher education level, there is no valid and reliable perception instrument about Sport Education. Research Objectives: This study aims to adapt the Sport Education Scale and provide validity and reliability evidence for used in the Indonesian context of higher education. Methods: The research method used survey. A convenient sample of 156 students who had been taught Sport Education participated in this study, who completed the Sport Education Scale. The research instrument used the Sport Education Scale. Data analysis techniques used confirmation factor analysis. Findings and Results: The results of this study confirmed that the Indonesian version of the Sport Education Scale for Higher Education can be used to assess the features of Sport Education in the context of Higher Education. The research in this study refers to it as the “Indonesian version of the Higher Education Sport Education Scale”. Conclusion: The Indonesian version of the Higher Education-Sports Education Scale implemented through the Sports Education curriculum is able to make a positive contribution to the development of Higher Education curriculum in Indonesia, especially those that adopt the Merdeka Belajar-Kampus Merdeka approach. In line with these findings, future research should focus on further investigation related to the application of the Sports Education Scale at educational levels other than Higher Education in Indonesia. In addition, recommendations for future research may include the development of sports teaching methods that focus on educational values and an increased understanding of the benefits of Sports Education in the context of Higher Education. This helps improve the quality of the Merdeka Belajar-Kampus Merdeka curriculum in Indonesia.